Peace and Security in the Western Balkans A Local Perspective - Dzuverovic, Nemanja; Stojarová, Věra (Taylor & Francis, 2023)
This book outlines the main security threats, actors, and processes in the Western Balkans following the dissolution of Yugoslavia. Exploring the state of peace and security in the region it asks if a stable peace is achievable. The comparative framework explores state perspectives - from Serbia, Montenegro, Northern Macedonia, Bosnia and Herzegovina, Albania, and Kosovo - alongside military, political-societal, economic, and environmental security concerns. The interplay of international actors is also considered. Academics, scholars, and practitioners who deal with Balkan issues, either as a focus or comparatively, and have interests in security and peace studies will find the volume invaluable along with students of political science, security studies, peace studies, area studies (Eastern European studies and/or Southeast European studies), and international studies in general.